Rancang Bangun Basis Data Sistem Informasi Pengelolaan Aset Berbasis Web Menggunakan Framework Laravel - Fischa Deanita Mabilaka; Rizky Parlika (Jurnal Penelitian Teknologi Informasi dan Sains, 2026)
The development of information technology has brought major changes in government agencies managing data and information, including in the KPKNL office. Asset data management that is still done manually often causes various obstacles, such as recording errors, delays in preparing reports, and difficulties in data validation. These conditions can affect the effectiveness and efficiency of the ongoing administrative process. The development of this system is carried out by designing using UML, designing databases with ERD, and implementing web applications. The main features included in this web system are asset data, activity logs, asset monitoring, and asset reports. This web-based system makes it easier to manage asset data in the office at KPKNL. This improves employee work efficiency, reduces recording errors, and makes it easier for users to access information. With this web application, the asset data collection process runs faster, more integrated, and very well documented.